2015
DOI: 10.3109/10641963.2015.1036058
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between white blood cells and hypertension in Chinese adults: The Cardiometabolic Risk in Chinese (CRC) study

Abstract: Increased blood pressure was associated with increased white blood cell count (adjusted p < 0.001) in a community-based health examination survey of adults in China (n = 39 282; aged 18-93 years). Adjusted odds ratios (95% confidence intervals) for hypertension across white blood cell count quintiles were 1.00, 0.99 (0.89-1.09), 1.11 (1.01-1.22), 1.09 (0.99-1.20), and 1.19 (1.08-1.31) (p for trend < 0.001). Body mass index and white blood cell count had an additive effect on systolic blood pressure (p for inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In recent years, white blood cells (WBCs) have been considered as an inflammatory factor (Chung et al, 2016). The elevated WBCs count has widely recognized in association with several diseases such as metabolic syndrome (Yang et al, 2017), cardiovascular disease (Lassale et al, 2018), diabetes (Gu et al, 2018), hypertension (Sun et al, 2015), non-alcoholic fatty liver (Chung et al, 2016), polycystic ovary syndrome (Papalou et al, 2015), infections and chronic inflammation (Dixon and O'Brien, 2006) and even mortality (Kabat et al, 2017). Today, the predictive value of WBCs for the diseases is considered similar to total cholesterol (Panagiotakos et al, 2005;Kabat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, white blood cells (WBCs) have been considered as an inflammatory factor (Chung et al, 2016). The elevated WBCs count has widely recognized in association with several diseases such as metabolic syndrome (Yang et al, 2017), cardiovascular disease (Lassale et al, 2018), diabetes (Gu et al, 2018), hypertension (Sun et al, 2015), non-alcoholic fatty liver (Chung et al, 2016), polycystic ovary syndrome (Papalou et al, 2015), infections and chronic inflammation (Dixon and O'Brien, 2006) and even mortality (Kabat et al, 2017). Today, the predictive value of WBCs for the diseases is considered similar to total cholesterol (Panagiotakos et al, 2005;Kabat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing quantity of sodium serves as an anticoagulant and bursting agent for WBCs as shown in Figure 3(c, d, e, f). WBCs count is elevated in hypertension (WHITWORTH, 2004, NAKANISHI et al, 2002, SUN et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension alters erythrocytes structure, reduces oxygen transport, increases blood viscosity and rouleaux formation (CICCO; PIRRELLI, 1999). Hypertension increases RBCs count and reduces MCV (SUN et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte level count reflected low-grade systemic inflammation. Leukocyte count could independently predict hypertension in Chinese adults 16 . Two studies shown that hyperuricemia correlated with leukocyte count 17,18 .…”
Section: Introductionmentioning
confidence: 99%